(untitled) (Journal of Medical Sciences, 2022)
Over one quarter of major congenital anomalies affect the heart. Delayed diagnosis of severe forms, especially after the neonatal period, is associated with up to twelve-fold increased mortality. Our study aims to assess the prevalence and pattern of congenital heart disease in high-risk neonates in southern Libya. A cross-sectional descriptive study was done at the pediatric echocardiography clinic of Sebha Medical Center from May 2019 to April 2020, and all newborns referred for echocardiographic screening were included. Over half of the congenital heart anomalies (58%) were of a simple type that might close spontaneously (PDA, VSD, ASD); 11% were severe forms that need early intervention ( AV Canal, CO A, TOF ). Early detection can save lives, so we recommend introducing universal postnatal echo screening for every newborn and also fetal echo screening for every mother with a high-risk pregnancy.